Arquétipos e memória: A gravura de Marcelo Grassmann - Pinto, Dalila dos Santos Cerqueira (2007)
Analysis of the brazilian artist Marcelo Grassmann engraving (1925 - ), as study of the relations of the Art with the areas of Analytical Psychology and Cultural History. The concepts of the Analytical Psychology of Carl Gustav Jung allow to identify in the Grassmann engraving, the structure of forms and archetypical representations of symbolic images coming from the unconscious collective mind, that is common patrimony to human being. Owing to the conceptualization of nachleben and pathosformeln of the art historian Aby Warburg, and the study of the archives of the memory and the notion of engrama, the possibility to establish the linking between works of art of diverse periods, artists and historical times, in a structure that today we define as net. Historical and individual contents, filling the archetype as empty forms are evidenced in the image. The research presents Marcelo Grassmann as a memory rescuer, elaborating in the wood engravings, lithographies and metal engravings, the reconstruction through the memory. It is the rescue of the memory of the history of a past transformed into to present, in the privileged space that is the Art. The work contributes with an interdisciplinary vision, in the conception of a science of the culture.